2020
DOI: 10.6061/clinics/2020/e1656
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanism of stem cells from human exfoliated deciduous teeth combined with hyperbaric oxygen therapy in type 2 diabetic rats

Abstract: OBJECTIVES: Mesenchymal stem cells (MSCs) are potentially ideal for type 2 diabetes treatment, owing to their multidirectional differentiation ability and immunomodulatory properties. Here we investigated whether the stem cells from human exfoliated deciduous teeth (SHED) in combination with hyperbaric oxygen (HBO) could treat type 2 diabetic rats, and explored the underlying mechanism. METHODS: SD rats were used to generate a type 2 diabetes model, which received stem cell therapy, HBO therapy, or both togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…55,56 SHEDmediated immunomodulation and islet function restoration have been documented in our previous reports, which potentially contribute to treatment of T2DM. 31,56 In this study, we also observed the…”
Section: Adverse Effectssupporting
confidence: 70%
See 4 more Smart Citations
“…55,56 SHEDmediated immunomodulation and islet function restoration have been documented in our previous reports, which potentially contribute to treatment of T2DM. 31,56 In this study, we also observed the…”
Section: Adverse Effectssupporting
confidence: 70%
“…The mechanisms underlying MSC-mediated therapy for diabetes have not been elucidated. It has been suggested that MSCs may directly differentiate into IPCs, [23][24][25] promote islet β-cell regeneration, 26,27,31 and improve insulin resistance, 31,[47][48][49] thus playing an important role in improving the glucose metabolism. In addition, regulation of the interplay between immune response and the microenvironment of islet cells may contribute to MSC-mediated therapy for diabetes.…”
Section: Adverse Effectsmentioning
confidence: 99%
See 3 more Smart Citations